The Model of Educational Reconstruction: Students’ Conceptual Knowledge on Solid State Chemistry Domain (Jurnal Pendidikan IPA Indonesia, 2018)
Solid state chemistry (SSC) concept is abstract yet makes it difficult for students. Considering students’ and scientist conception in designing a learning sequence, it is important to make scientific knowledge to be comprehensible for students. Model of Educational Reconstruction (MER) was adopted to define learning in order to develop students’ Conceptual Knowledge (CK) of the SSC concept. A sequence of learning activities was designed based on the MER.  The purpose of this study was to examine the use of MER in developing students’ CK. One group pre- and post-test experimental design employed in this study. CK on SSC structured essay test consisting of 26 items were developed to measure students’ CK before and after their involvement in learning. Paired sample t-tests were employed and the results showed significant differences in the overall domain-knowledge (p .001).  In detail, students’ CK categorized into complete (C), incomplete (IC), misconception (M), incorrect (I), and no answer (NA). After the intervention, the number of students that answered correctly increased (57,4% complete and 21% incomplete). This study showed that MER was an effective learning design to develop students’ conceptual knowledge of chemistry concepts.